Hybrid functional calculations of optoelectronic properties of ultra-wide bandgap LiSmO2: A first-principle study. (1st February 2022) - Shah, Syed Sarmad Ali; Muhammad, Nisar; Murtaza, G.; Khan, Afzal; Ashraf, Muhammad Waqar; Khan, Shamim
Abstract: Due to their numerous superior properties, the advent of ultra-wide bandgap (UWBG) semiconductors with bandgaps noticeably greater than 3.4 eV ushers in a new era of advancement in a variety of fields. UWBG have enormous potential for electronic device advancement, as device performance improves nonlinearly as band gap values increase. To comprehend their unique properties, detailed knowledge of the nature of materials and their role in determining the properties is required. We used density functional theory (DFT) in conjunction with an accurate screened-hybrid functional to determine the electronic and optical properties of Lithium Samarium Oxide (LiSmO2 ). The electronic structure calculations revealed an indirect bandgap of 5.14 eV, providing a material platform for expanding the semiconductor industry beyond the well-established wide bandgap semiconducting materials. Following that, we investigated the optical properties and discovered that LiSmO2 was transparent in the infrared and visible regions, indicating that it could be used as an infrared window material. DFT calculations of the structural, electronic, and optical properties of LiSmO2 were carried out using two different types of generalized gradient approximations, namely PBE-GGA and the Hyed-Scuseria-Enzerhof (HSE06) hybrid functionals. When compared to the results of PBE, HSE06 calculates structural and electronic properties that are closer to the experimental values. The band gap as determined by HSE06 is 5.14 eV. A 1.42 eV shift in the band gap of LiSmO2 was observed when the hybrid functional was used instead of PBE-GGA. The static dielectric function ε 1 is estimated to be approximately 3.6 eV. Our findings place LiSmO2 at the forefront of the quest for the next generation of semiconductor materials that enable more efficient energy optoelectronics and power electronics by reducing electric power losses, UV mirror, and solar blind applications. Highlights: To find the accurate band gap value, we employed HSE06 approximation for the first time. We discovered that the functional choice has a significant effect on the electronic structure. The static dielectric function ε 1 is calculated around 3.7 eV. The maximum α ( ω ) value determined in this work agrees well with that of experiment. The n (ω) of LiSmO2 near band gap value is larger than that of GaN.